PENYULUHAN TENTANG MENCEGAH LUKA DAN SENAM DIABETES PADA PENDERITA DIABETES MELLITUS DI WILAYAH KERJA PUSKESMAS MARTAPURA KABUPATEN BANJAR - Isnaniah - Isnaniah; Hapisah Hapisah; Rubiati Hipni; Rusmilawaty Rusmilawaty; Tut Barkinah (Jurnal Bakti untuk Negeri, 2022)
According to WHO in 2006 at least 171 million people had diabetes. By 2030. In Indonesia, Incidence will double. in the 2000s, there were 125 million people over the age of 20. Based on this pattern of population growth, it is estimated that in early 2020 the Indonesian population aged over 20 years is around 178 million people and it is assumed that there will be an increase in the prevalence of DM incidence of around 8.2 million people. Purpose: The purpose of this Community Service is to provide counseling on how to prevent injuries in people with diabetes mellitus and provide training on diabetes exercise for people with diabetes mellitus. Methods: The method used is lectures and discussions to provide an understanding of how to prevent wounds in people with Diabetes Mellitus as well as simulations and demonstrations by providing skills about diabetes gymnastics. Results: Community service can be carried out with permission from the Martapura Health Center, Banjar Regency with 2 counseling activities and skills provision. Conclusion: Counseling on wound prevention for Diabetes Mellitus patients has been carried out twice using LCD media and pamphlets, and Diabetes Exercises for diabetics can be done by watching videos and pamphlets given led by one instructor. Keywords: Diabetes Mellitus, Diabetes Gymnastics, Wounds